2020
DOI: 10.1111/1759-7714.13367
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of response in metastatic NSCLC during PD‐1 or PD‐L1 inhibitor therapy: Comparison of the RECIST 1.1 and iRECIST criteria

Abstract: Background Immunotherapy plays an important role in advanced non‐small cell lung cancer (NSCLC). However, radiological evaluation is challenging due to the potential inflammatory effects of immunotherapy, which can lead to atypical response patterns. Identifying these atypical responses is critical to making treatment decisions and prognostication. Methods We performed a retrospective analysis of consecutive advanced NSCLC patients treated with immunotherapy (alone or in combination). We collected patients' cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…The study search process is shown in Figure 1 . The characteristics of the 11 studies [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ] including 6210 patients are summarized in Table 1 . One study was a pooled analysis of individual patient data (IPD) from 14 Food and Drug Administration (FDA)-approved randomized controlld trials (RCTs), one was an RCT, one was a phase II clinical trial, and eight were observational studies (1 prospective study and 7 retrospective studies).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study search process is shown in Figure 1 . The characteristics of the 11 studies [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ] including 6210 patients are summarized in Table 1 . One study was a pooled analysis of individual patient data (IPD) from 14 Food and Drug Administration (FDA)-approved randomized controlld trials (RCTs), one was an RCT, one was a phase II clinical trial, and eight were observational studies (1 prospective study and 7 retrospective studies).…”
Section: Resultsmentioning
confidence: 99%
“…The following data were extracted: (a) study characteristics including authors, year of publication, and study design; (b) demographic and clinical characteristics of the patients including sample size, type of cancer, and type of ICIs; (c) response-related endpoints based on RECIST 1.1 and iRECIST: ORR and iORR, and DCR and iDCR; and (d) data required to estimate PFS and iPFS as survival endpoints based on RECIST 1.1 and iRECIST, respectively [ 30 , 31 ]. In five studies [ 14 , 15 , 18 , 20 , 21 ], according to methods proposed by Guyot et al, individual patient data were reconstructed by extracting data from the Kaplan–Meier curves using digital software (WebPlotDizitizer) to estimate the time-dependent probability of PFS [ 27 ]. Definitions of each endpoint are detailed below.…”
Section: Methodsmentioning
confidence: 99%
“…In NSCLC patients continuing immunotherapy beyond progression had significantly prolonged OS. 36 The newly developed iRECIST criteria might be a method to cope with this problem, but have not been established in prospective clinical trials so far. Also, in HNSCC a secondary analysis of the CheckMate-141 trial identified responses after initial progression.…”
Section: Discussionmentioning
confidence: 99%
“…Along with the deepening understanding of NPC, the TNM staging system, RECIST and NCCN guidelines have changed significantly ( 12 , 23 ). Compared with early two-dimensional RT, the application of IMRT technology has significantly improved the treatment of NPC ( 126 ).…”
Section: Npc Biomarkers Discovered Through Metabolomicsmentioning
confidence: 99%
“…For example: i) Some patients still have tumor recurrence or distant metastasis after receiving radical RT or IC+CCRT/CCRT+AC, indicating that a more effective treatment should be developed (16)(17)(18)(19); ii) IC+CCRT improves the OS and DMFS of patients with LA-NPC to a limited degree, but most patients do not benefit from it, suggesting overtreatment (13)(14)(15); iii) patients have poor tolerance to toxic side effects of the treatment, which could lead to delays or interruptions in treatment, thus increasing the risk of tumor progression or drug resistance (1,(20)(21)(22); and iv) the clinical use of Response Evaluation Criteria in Solid Tumors (RECIST) can only provide a reference for the NPC treatment effect evaluation through generalized remission or progression, and cannot provide quantifiable prediction indexes for NPC recurrence and metastasis. Moreover, the prognosis model based on the TNM staging system cannot provide an objective assessment for the risk of disease progression for patients with NPC (23,24). These problems indicate issues regarding NPC diagnosis, treatment and prognosis, and suggest the need for individualized treatment.…”
Section: Introductionmentioning
confidence: 99%